Buildup from birth onward of short telomeres in human hematopoietic cells - Lai, Tsung‐Po; Verhulst, Simon; Savage, Sharon A.; Gadalla, Shahinaz M.; Benetos, Athanase; Toupance, Simon; Factor‐Litvak, Pam; Susser, Ezra; Aviv, Abraham (Aging cell, 2023)
Telomere length (TL) limits somatic cell replication. However, the shortest among the telomeres in each nucleus, not mean TL, is thought to induce replicative senescence. Researchers have relied on Southern blotting (SB), and techniques calibrated by SB, for precise measurements of TL in epidemiological studies. However, SB provides little information on the shortest telomeres among the 92 telomeres in the nucleus of human somatic cells. Therefore, little is known about the accumulation of short telomeres with age, or whether it limits the human lifespan. To fill this knowledge void, we used the Telomere‐Shortest‐Length‐Assay (TeSLA), a method that tallies and measures single telomeres of all chromosomes. We charted the age‐dependent buildup of short telomeres (<3 kb) in human hematopoietic cells from 334 individuals (birth‐89 years) from the general population, and 18 patients with dyskeratosis congenita‐telomere biology disorders (DC/TBDs), whose hematopoietic cells have presumably reached or are close to their replicative limit. For comparison, we also measured TL with SB. We found that in hematopoietic cells, the buildup of short telomeres occurs in parallel with the shortening with age of mean TL. However, the proportion of short telomeres was lower in octogenarians from the general population than in patients with DC/TBDs. At any age, mean TL was longer and the proportion of short telomeres lower in females than in males. We conclude that though converging to the TL‐mediated replicative limit, hematopoietic cell telomeres are unlikely to reach this limit during the lifespan of most contemporary humans. Population studies have principally focused on the role of mean telomere length in human health and longevity. The availability of new telomere length measurement techniques enables examining the relations between the shortest telomeres and human diseases.